Modern Missionary Chinese Periodicals and the Eastward Spread of Western Law - XU, Chunxi (Journal of Research for Christianity in China (JRCC), 2025)
Modern missionaries primarily disseminated Western legal systems in China through three channels: translating and authoring legal texts; publishing newspapers and journals featuring articles introducing Western law; and establishing church-affiliated universities offering systematic legal instruction. Among these, the dissemination of Western legal thought via periodicals played the most extensive role and exerted the broadest influence in the eastward transmission of Western law. From 1815, when missionary Robert Morrison of the London Missionary Society and his assistant James Milne collaborated with Chinese collaborator Liang Fa to establish China's first periodical, the Monthly Record of the World, until 1951 when church publications in mainland China were taken over—a span of 136 years—missionaries from Western nations founded over a thousand newspapers and magazines in China. These publications disseminated extensive knowledge on Western political constitutions, political systems, and legal institutions. This paper explores the role of missionary-founded publications in the eastward transmission of Western law. It begins by outlining the history of missionary-founded publications in China, then examines the dissemination of Western law through periodicals such as the Monthly General Record of the East and West Oceans, The Far and Near Treasures, The Gazette of All Nations, and Records of Chinese and Western Observations. It concludes by analyzing the historical significance of these Chinese-language missionary publications in the process of Western law's eastward transmission.